Physical chemistry - Rudneva, S. I.; Sakhnenko, N. D.; Djenyuk, A. V. (My University, 2018)
Brief summary of the traditional sections of physical chemistry, such as: thermodynamics, chemical and phase equilibrium, electrochemistry and kinetics are presented. The most difficult problems are studied in detail. The presentation of such complex topics is accompanied by the analysis of examples and problems, and the control tasks are given in the main sections of physical chemistry. The manual is addressed to students of chemical engineering directions of education.
Keywords: practical course; chemical thermodynamics; chemical equilibrium; phase equilibria; electrochemistry; chemical kinetics